High-Intensity Focused Ultrasound Ablation for Primary or Salvage Prostate Cancer Therapy: Initial Outcomes in the Veteran Healthcare Setting - Sagar Patel; Ali Antar; Aly Alrabaa; Gal Saffati; Broderick Fleming; Neel Srikishen; Jeremy Slawin; Jennifer Taylor; Jeffrey Jones (Life)
High-Intensity Focused Ultrasound (HIFU) provides comparable oncologic, erectile, and urinary outcomes to standard-of-care options for localized prostate cancer. This study reports the largest United States series of HIFU in veterans for both primary and salvage therapies. We retrospectively analyzed the outcomes of 43 veterans treated at the Michael E. DeBakey Veterans Affairs Medical Center from 2018 to 2022. Primary endpoints included prostate-specific antigen (PSA) reduction and local recurrence rates. Secondary endpoints included 30-day complications, Sexual Health Inventory for Men (SHIM), and American Urological Association Symptom Score (AUASS). In our study, 31 veterans (72.1%) received primary treatment and 12 (27.9%) received salvage therapy, with a median follow-up of 23 and 25 months, respectively. Median PSA nadir was 0.16 for primary and 0.12 for salvage groups, with PSA reduction stable over 30 months. Local recurrence occurred in 16.1% of primary and 16.6% of salvage patients. SHIM scores and AUASS were not statistically different before and after HIFU therapy. Short- and intermediate-term results suggest HIFU is a safe and effective treatment option with excellent potency and preserved urinary function, as well as adequate oncological control for primary and salvage therapies for localized prostate cancer in veterans.